Validation of the Open Source Code_Aster Software Used in the Modal Analysis of the Fluid-filled Cylindrical Shell - B D. Kashfutdinov (Nauka i Obrazovanie, 2017)
The paper deals with a modal analysis of the elastic cylindrical shell with a clamped bottom partially filled with fluid in open source Code_Aster software using the finite element method. Natural frequencies and modes obtained in Code_Aster are compared to experimental and theoretical data. The aim of this paper is to prove that Code_Aster has all necessary tools for solving fluid structure interaction problems. Also, Code_Aster can be used in the industrial projects as an alternative to commercial software. The available free pre- and post-processors with a graphical user interface that is compatible with Code_Aster allow creating complex models and processing the results. The paper presents new validation results of open source Code_Aster software used to calculate small natural modes of the cylindrical shell partially filled with non-viscous compressible barotropic fluid under gravity field. The displacement of the middle surface of thin shell and the displacement of the fluid relative to the equilibrium position are described by coupled hydro-elasticity problem. The fluid flow is considered to be potential. The finite element method (FEM) is used. The features of computational model are described. The resolution equation has symmetrical block matrices. To compare the results, is discussed the well-known modal analysis problem of cylindrical shell with flat non-deformable bottom, filled with a compressible fluid. The numerical parameters of the scheme were chosen in accordance with well-known experimental and analytical data. Three cases were taken into account: an empty, a partially filled and a full-filled cylindrical shell. The frequencies of Code_Aster are in good agreement with those, obtained in experiment, analytical solution, as well as with results obtained by FEM in other software. The difference between experiment and analytical solution in software is approximately the same. The obtained results extend a set of validation tests for Code_Aster in the field of aerospace systems. Using the free software to analyze the aerospace system components allows enterprises to diminish dependency on the commercial software, reduce the cost of software usage, and adapt the open source software to the specific problems.